2019
DOI: 10.1016/j.jtcvs.2018.11.130
|View full text |Cite
|
Sign up to set email alerts
|

Carinal surgery: A single-institution experience spanning 2 decades

Abstract: Objectives: Complete resection of neoplasms involving the carina are technically challenging and have high operative morbidity and mortality. This study examines the last 2 decades of clinical experience at our institution.Methods: Medical records were retrospectively reviewed between 1997 and 2017 to identify all patients who underwent carinal resection. Primary outcome measures include risk factors for complications and overall survival.Results: In total, 45 carinal resections were performed with a median fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 35 publications
(54 reference statements)
1
33
0
4
Order By: Relevance
“…These differences may have negatively impacted our operative and survival outcomes in comparison with other studies. A recent report by Costantino et al described excellent operative mortality of 6.8%; however, the mortality after CP was 12% in the same report (16). In comparison, Eichhorn et al used a patient cohort very similar to our study cohort, and our post-2000 results are equivalent or better than their reported outcomes of 3% 30-day mortality, 40% 3-year OS, and 31% of 5-year OS (12).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…These differences may have negatively impacted our operative and survival outcomes in comparison with other studies. A recent report by Costantino et al described excellent operative mortality of 6.8%; however, the mortality after CP was 12% in the same report (16). In comparison, Eichhorn et al used a patient cohort very similar to our study cohort, and our post-2000 results are equivalent or better than their reported outcomes of 3% 30-day mortality, 40% 3-year OS, and 31% of 5-year OS (12).…”
Section: Discussionsupporting
confidence: 55%
“…As numerous articles have described, patient selection, perioperative management including anesthetic technique, and surgical technique are key factors for achieving favorable short-term surgical and long-term oncologic outcomes after carinal surgery (3,4,(9)(10)(11)(12)(13)(14)(15)(16). Our outcomes showed clear improvements over the two decades of the study, and therefore analysis of these factors between the two study periods was performed.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Even in 2000 decade, the rate of complications was reported with a wide variability, with a top value of 50.8% (45). In recent years and in centers with experienced surgeons, and with the advent of minimally invasive approaches, the mortality rate is lower with overall postoperative 30-day rates between 2.7% to 10.9%, but still with a wide range of morbidity (12,46,47). Also, reports of new techniques like carinal resections with lung parenchyma-sparing for NSCLC by uniportal VATS give a new perspective to this kind of complex cases.…”
Section: The Rise Of the Uniportal Approachmentioning
confidence: 99%
“…Lateral tracheal fenestration was performed above the level of carina. The tracheal opening was at least 1-1.5 cm 2 in size and created entirely on the cartilaginous wall or partly including the edge between cartilaginous and membranous wall (6,7). The anastomosis between graft bronchus and lateral wall of trachea was started using parachute principle.…”
Section: Surgical Techniquementioning
confidence: 99%